Aerosol properties over the ocean from PARASOL multiangle photopolarimetric measurements - Hasekamp, Otto P.; Litvinov, Pavel M.; Butz, André (Journal of geophysical research. Atmospheres, 2011)
In order to make full use of the capability of satellite instruments that measure intensity and polarization properties of reflected light at multiple viewing angles and multiple wavelengths, algorithms are needed that consider a continuous parameter space for aerosol microphysical properties (size distribution and refractive index) and properly account for land or ocean reflection by retrieving land and ocean parameters simultaneously with aerosol properties. In this paper we apply a retrieval algorithm based on these principles to PARASOL measurements over the ocean. We fit a radiative transfer model for a coupled atmosphere-ocean system to the PARASOL measurements and retrieve the oceanic chlorophyll a concentration, wind speed in two directions, and fractional foam coverage in addition to all parameters related to a bimodal aerosol model. The retrieved values for aerosol optical thickness (AOT) and Angstrom exponent agree well with Sun photometer measurements of the Aerosol Robotic Network (AERONET), and the Single Scattering Albedo (SSA) agrees well with the AERONET diffuse sky inversion product. We demonstrate that the PARASOL polarization measurements improve agreement with AERONET compared to intensity-only retrievals. Also, based on comparison of our forward radiative transfer calculations and the PARASOL measurements, we discuss the high potential of multiangle, multispectral photopolarimetric measurements for the simultaneous retrieval of aerosol and cloud properties.